Analysis of Mass Transfer During Natural Gas Purification Process in a Vertical Tube - Koyun, Tansel; Kunduz, Mehmet; Öztop, Hakan Fehmi (Gazi Univ, 2014)
The effects of axial and radial velocities on mass transfer during the purification of natural gas in a vertical pipe are studied numerically. The natural gas flowing inside a vertical channel and monoethanolamine (MEA) flowing as a film along the inner wall of the channel is taken together for the purification process. The direction of laminar flow of both fluids is gravity direction. The environment is assumed as isothermal. Comparisons are performed for the interface (wall) between the film and the gas in the presence and absence of axial mass flow. Grams' finite difference formulation are used to solve governing equations and solved by using Grams' package code. It is found that the interface axial velocity effect on mass transfer can be neglected for low Reynolds numbers.
Keywords: Natural gas; Purification; Mass transfer; Reynolds number